THE IMPACT OF LOGISTICS INFRASTRUCTURE ON THE COMPETITIVENESS OF AGRICULTURAL ENTERPRISES IN THE GRAIN SECTOR - Shcherbak, Denys (Public Management and Policy, 2025)
The article examines the current impact of logistics infrastructure on the formation and strengthening of the competitiveness of agricultural enterprises operating in the grain sector. The aim of the article is to analyze how logistics infrastructure impacts the competitiveness of agricultural enterprises in the grain sector, identify key logistics factors that enhance the efficiency of foreign economic activity, and propose directions for its improvement to strengthen the position of Ukrainian grain exporters on the global market. It is emphasized that in the conditions of globalization and integration into international markets, agricultural producers are faced with the need not only to ensure high quality products, but also to effectively organize the processes of transportation, storage, transshipment and export clearance. It is determined that the availability of modern logistics infrastructure – including elevators, transport corridors, port terminals and digital platforms – directly affects the reduction of costs, acceleration of capital turnover, compliance with delivery deadlines and satisfaction of the requirements of external partners. The key challenges faced by Ukrainian grain companies are analyzed: insufficient level of infrastructure, concentration of transshipment capacities in certain regions, logistical congestion and dependence on foreign policy factors. Directions for modernization of the logistics system as a tool for increasing competitive advantages in the international market are proposed: investments in multimodal transportation, development of digital logistics, public-private partnership and improvement of the regulatory framework. The conclusion is made that logistics is becoming a strategic resource of agrarian business, on which not only export efficiency depends, but also the overall stability of enterprises in turbulent economic conditions.